2020
DOI: 10.1080/07391102.2020.1763199
|View full text |Cite
|
Sign up to set email alerts
|

In silico study the inhibition of angiotensin converting enzyme 2 receptor of COVID-19 by Ammoides verticillata components harvested from Western Algeria

Abstract: The objective of this present study is to focus on the in silico study to screen for an alternative drug that can block the activity of the angiotensin converting enzyme 2 (ACE2) as a receptor for SARS-CoV-2, potential therapeutic target of the COVID-19 virus using natural compounds (Isothymol, Thymol, Limonene, P-cymene and c-terpinene) derived from the essential oil of the antiviral and antimicrobial plant Ammoides verticillata (Desf.) Briq. which is located in the occidental Algeria areas. This study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
110
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 42 publications
2
110
0
2
Order By: Relevance
“…While, structural composition of domain III mainly consists of alpha-helices (Anand et al, 2005;Yang et al, 2005;Lu et al, 2006;Jin et al, 2020), protease has been characterized as one of the potential drug targets among coronaviruses (Anand et al, 2003). In this sense, many recent studies suggested that the selection of various FDA-approved antiviral compounds may yield promising results against COVID-19 infection (Chang et al, 2016;Chang et al, 2020;Contini, 2020;Gonzalez-Paz et al, 2020;Khan et al, 2020;El ky, 2020a;Islam et al, 2020;Sinha et al, 2020;Wahedi et al, 2020;Kundu et al, 2020;Das et al, 2020;Abdelli et al, 2020 ). Chang et al, 2020 reported that chloroquine, an older antimalarial drug, has ability to inhibit the viral 3CLprotease activity.…”
Section: Introductionmentioning
confidence: 99%
“…While, structural composition of domain III mainly consists of alpha-helices (Anand et al, 2005;Yang et al, 2005;Lu et al, 2006;Jin et al, 2020), protease has been characterized as one of the potential drug targets among coronaviruses (Anand et al, 2003). In this sense, many recent studies suggested that the selection of various FDA-approved antiviral compounds may yield promising results against COVID-19 infection (Chang et al, 2016;Chang et al, 2020;Contini, 2020;Gonzalez-Paz et al, 2020;Khan et al, 2020;El ky, 2020a;Islam et al, 2020;Sinha et al, 2020;Wahedi et al, 2020;Kundu et al, 2020;Das et al, 2020;Abdelli et al, 2020 ). Chang et al, 2020 reported that chloroquine, an older antimalarial drug, has ability to inhibit the viral 3CLprotease activity.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular docking study revealed it to form a stable interaction with ACE2 receptor. Based on the results of the study, authors suggested that Ammoides verticillata essential oil components could slow down the spread of infection by blocking the entry of the virus in to the cell [ 97 ].…”
Section: Potential Of Medicinal Plants Against Covid-19mentioning
confidence: 99%
“…Identified first time in Wuhan city of China in late December 2019 (Aanouz et al, 2020;Elfiky & Azzam, 2020;Elmezayen et al, 2020;Enayatkhani et al, 2020;Fausto et al, 2020;Ghosh et al, 2020;Muralidharan et al, 2020;Phulen et al, 2020;Rajib et al, 2020;Rothan & Byrareddy, 2020;Rowan & Laffey, 2020;Salman et al, 2020;Sourav et al, 2020;Umesh et al, 2020), Covid19 is a respiratory disease that is caused by the new coronavirus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-Cov-2) 2019 (Abdelli et al, 2020;Rakesh et al, 2020;Rameez et al, 2020;World Health Organization, 2020). Covid19 is the name given by the World Health Organization (WHO) on 11 February 2020 (World Health Organization, 2020).…”
Section: Introductionmentioning
confidence: 99%